Pengaruh Pengetahuan, Kualitas Produk, Promosi, dan Kualitas Pelayanan Terhadap Keputusan Nasabah Menabung di Bank 9 Jambi Syariah Kota Jambi - Utami Ria Rahayu; Usdeldi Usdeldi; Anzu Elvia Zahara (Pusat Riset dan Inovasi Nasional, 2026)
The background of this research is to examine the services at Bank 9 Jambi Syariah, Jambi City to support good service with the variables taken by the author. The purpose of this study is to examine the influence of knowledge, product quality, promotion, and service quality on saving decisions at Bank 9 Jambi Syariah, Jambi City. This is a quantitative study that utilizes the Total Sampling method of 100 respondents among customers at Bank 9 Jambi Syariah, Jambi City. At the inferential statistical analysis stage, data analysis is assisted by a statistical program using SEM analysis, namely the Smart-PLS analysis computer program. The data collection technique uses a questionnaire distribution method. The results of this study are: 1) there is a significant and positive influence of knowledge on customer saving decisions at Bank 9 Jambi Syariah. 2) there is a significant and positive influence of Product Quality on customer saving decisions at Bank 9 Jambi Syariah. 3) there is a significant and positive influence of promotion on customer saving decisions at Bank 9 Jambi Syariah. 4) there is a significant and positive influence of service quality on customer saving decisions at Bank 9 Jambi Syariah.